Objective severity classification of unilateral cleft lip nasal deformity using nostril width, alar facial symmetry ratio, and columellar angle to justify surgical outcomes - Yap, Pauline; Prasetyono, Theddeus Octavianus Hari; Wan Sulaiman, Wan Azman; Mohamad Shah, Nurul Syazana; Mat Johar, Siti Fatimah Noor; Basiron, Normala; Harun Nor Rashid, Shawaltul Akhma; Halim, Ahmad Sukari; Lian, Ho Hui (Springer, 2025)
Introduction: Unilateral cleft lip nasal (UCL/N) deformity severity presents complex anatomical challenges, with surgical outcomes influenced by preoperative status. Existing classification systems for UCL/N lack standardization, relying on subjective clinical assessments or isolated anthropometric measures that fails to assess anatomical deformity comprehensively. This limits their utility in objectively stratifying deformity severity and justifying postoperative outcomes. To address this gap, we developed UCL/N Deformity Rating Scale (DRS), an objective classification tool incorporating three validated anatomical indicators: alar facial symmetry ratio, nostril width ratio, and columellar angle. This study aims to (1) validate the scale’s reliability for grading preoperative anatomical severity and (2) establish its clinical applicability by correlating preoperative grades with postoperative aesthetic outcomes, thereby justifying surgical outcomes, not evaluating institutional surgical performance. Methods: This retrospective cohort study (Level III evidence) analyzed standardized, ethically approved two-dimensional photographs from 50 UCL/N pre- and postoperative patients. All photographs were deidentified, randomized, and independently assessed by three consultant plastic surgeons and three trainees to evaluate interrater reliability using the intraclass correlation coefficient (ICC). The DRS was applied to grade pre- and postoperative severity, and 12 paired cases were analyzed to correlate these grades with postoperative aesthetic outcomes, demonstrating the justification system’s clinical applicability. Results: Assessments of key anatomical indicators showed consistent agreement across pre- and postoperative evaluations, with no significant differences (p > 0.05). The UCL/N DRS demonstrated good interrater reliability (ICC = 0.64–0.72). In 12 cases, outcomes matched or surpassed predictions: 5 matched, 7 exceeded, and none were substandard. This demonstrates the system’s clinical applicability as a standardized tool to grade primary deformity severity and justify surgical outcomes by linking preoperative severity to postoperative results. Conclusions: Strong interrater reliability across assessors support the UCL/N DRS as a reliable objective tool for assessing the UCL/N anatomical severity and justifying the post-operative outcome. Level of Evidence III: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.